Investigating Built Environment Indicators to Develop a Local Walkability Index - Menna Tarek; Ghada Farouk Hassan; Abeer Elshater; Mohamed Elfayoumi (Journal of Contemporary Urban Affairs, 2021)
Many studies have been conducted over the last 20 years to determine and measure factors that affect the walkability of city streets. Walkability is an essential factor in deciding whether a city is green or sustainable. This paper creates a comprehensive walkability index by analysing built environmental indicators that affect walkability. This research was conducted on mixed land use streets in Cairo, Egypt, combining the results from an online survey and a walkability assessment model developed by multi-criteria decision analysis techniques. The results were based on a three-pillar approach starting with the theoretical background to frame the walkability indicator, numerical assessment over the Egyptian cases using a multi-criteria decision-making (MCDM) technique and a qualitative user perception survey. Our results confirm that determining to what extent Cairo’s streets are walkable is crucial to enhancing pedestrians’ perceptions of the walking environment. Furthermore, the results illustrated the essential factors within the built environment indicators that influence pedestrian walking behaviour.